Perceptions of the University of the Philippines Manila College of Dentistry Batch 2013-2014 students and their professors on the contributing factors for their failure in specific laboratory courses - Subido, Nathalya Bmay A.
Despite the success of the University of the Philippines Manila College of Dentistry in producing competent dentists and board topnotchers, it continues to be plaqued by a high attrition rate among its students with many of them not graduating on time. The study aims to determine the perceptions of the students, as well as the professors' regarding their failure in such laboratory courses. Knowing that the failure of the students comes with a high price, this study was undertaken in the hope that a clearer understanding of the problem could bring the college closer to a solution. Methods: Forty-eight UPCD Batch 2013-2014 participants volunteered to participate in a survey on the factors which causes failure in the laboratory courses. Four students who failed in the identified courses participated in the reflection paper writing while 3 regular and 3 irregular students joined two separate focus group discussions. Furthermore, 4 faculty members of Dentistry 131.1, 132.1 and 141.1 were personally interviewed to determine the professors' view on the failure in laboratory problem. The data collected were analyzed using descriptive statistics and content analysis. Results: There are common influential intrinsic factors according to both passers and failed students namely: poor time management, intimidation towards their professor, inadequate psychomotor skills and high difficulty of the course. Likewise, the most influential extrinsic factors identified by the students are: differing opinion from the faculty and the faculty's current frame of mind affecting the way they evaluate. On the other hand, there are factors identified by the failed students alone, these are: the lack of practice in order to hone psychomotor skills and the mismatch in the teaching-learning style. There are some factors that the faculty and the student shares. They see that the students do not maximize their time in every laboratory session and they are too nervous to approach them. They also observe that each student has different pace in learning or acquiring psychomotor skills and some of them really needs more practice in order to acquire the skill and concepts of the course. The faculty observes other factors that are as well influential to the student's failure which are: the lack of discipline and lack of fair assessment of their ability. Conclusion: The phenomenon of students getting delayed as early as pre-clinical level as a result of their failure in the laboratory courses in complex and multi-factorial. The identified contributory factors could be addressed and a remedial solution could be reached. It will, however, take the cooperation of all parties concerned to solve the problem of high failure rates in the laboratory classes.